Clinical and immunogenetic characteristics of European multicase rheumatoid arthritis families. Issue 6 (1st June 2001) - Balsa, A; Barrera, P; Westhovens, R; Alves, H; Maenaut, K; Pascual-Salcedo, D; Cornélis, F; Bardin, T; Riente, L; Radstake, T R D J; de Almeida, G; Lepage, V; et al.
Abstract : OBJECTIVE: To describe the characteristics of a new set of European families with affected sib pairs (ASP) collected by the European Consortium on Rheumatoid Arthritis Families (ECRAF) to replicate the results of our first genome scan. Potential gradients for disease severity in Europe and concordance within families were studied. PATIENTS AND METHODS: From 1996 to 1998 European white families with at least two affected siblings were enrolled in the study. Demographic (sex, age at onset), clinical data (rheumatoid factor (RF), disease duration, erosive disease, extra-articular features (EF)), and HLA-DRB1 oligotyping were analysed. RESULTS: 565 patients with rheumatoid arthritis (RA), belonging to 271 families including 319 affected sib pairs (ASP) were collected. Belgium, France, Italy, the Netherlands, Portugal, and Spain contributed 20, 96, 52, 24, 9, and 70 families, respectively. Sex (78% women), age at onset (mean 44 years), and RF positivity (79%) were similar among the countries. Differences were found in disease duration (11–18 years) and in the prevalence of erosive disease (70–93%), nodules (15–44%), subjective Sjögren's syndrome (5–38%), and EF (3–16%) (p<0.05 in all cases). A total of 22% RA sibs were shared epitope (SE) negative, whereas 47% and 30% carried one and two SE alleles respectively. Carriage of SE differed widely among countries (p<0.0001): no SE alleles (6–36%), one allele (43–60%), and two alleles (20–39%). SE encoding alleles were mainly DRB1*04 in the Netherlands and Belgium, whereas SE carriage was less common and evenly distributed between DRB1*01, *04, and *10 in Mediterranean countries. No concordance within families was found either in age/calendar year of onset (intraclass correlation coefficient <0.50) or in clinical and radiological features (κ<0.22). CONCLUSIONS: The differences in RA characteristics between European countries and within families underline the heterogeneity of the disease. No clear cut gradient of disease severity was seen in Europe.